Synthesis, Crystal Structure, and DFT Study of N′-(2, 4-Dinitrophenyl)-2-Fluorobenzohydrazide. (6th August 2013) - Saeed, Aamer; Arshad, Ifzan; Flörke, Ulrich
Abstract : A new hydrazide derivative N ′-(2, 4-dinitrophenyl)-2-fluorobenzohydrazide was synthesized and characterized by NMR and IR spectroscopy. The molecular structure was also studied by X-ray diffraction, and the results of the optimized molecular structure are presented and compared with density functional methods with 631-G basis set. The calculated results show that the optimized geometry can well reproduce the crystal structural parameters, for example, bond lengths and angles show good agreement with the experimental data.